In vitro Effect of Geranylgeraniol (GGOH) on Bisphosphonate-Induced Cytotoxicity of Oral Mucosa Cells - Rattanawonsakul, Krit; Bullock, George; Bolt, Robert; Claeyssens, Frederik; Atkins, Simon; Hearnden, Vanessa (Frontiers in Oral Health, 2022)
Medication-related osteonecrosis of the jaw (MRONJ) is an often-severe complication found in patients receiving bisphosphonates in the management of Paget’s, osteoporosis and metastatic cancer. Mucosal breakdown with bone exposure is a primary clinical presentation of MRONJ linked to the inhibitory effect of nitrogen-containing bisphosphonates (N-BP) on the mevalonate pathway. Geranylgeraniol (GGOH) has demonstrated a rescue effect on N-BP-treated osteoclasts but the biological effects on oral soft tissues and cells remain unclear. This study aimed to determine whether GGOH could restore the viability of oral mucosa cells from bisphosphonate induced toxicity in vitro. Primary oral fibroblasts and keratinocytes were exposed to different GGOH concentrations or GGOH in combination with two nitrogen-containing bisphosphonates, zoledronic acid (ZA) or pamidronic acid (PA), for 72 hours. The metabolic activity of each cell type was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. GGOH without bisphosphonates significantly reduced the metabolic activity of oral mucosa cells. Fibroblasts treated with GGOH and ZA in combination showed a slight increase in metabolic status compared to fibroblasts treated with ZA alone, however this positive effect was not observed in keratinocytes. In the presence of PA, GGOH was unable to increase the metabolic activity of either cell type. These findings demonstrate that GGOH is toxic to oral mucosa cells and that GGOH was not able to prevent bisphosphonate induced toxicity. These data show that GGOH does not have therapeutic potential for bisphosphonate-induced soft tissue toxicity in MRONJ and the use of GGOH as an MRONJ treatment should be strongly reconsidered.